Realización de un documental sobre la importancia del idioma kichwa en los estudiantes de la carrera de Comunicación Social de la Universidad Politécnica Salesiana. Campus El Girón. Sede Quito. - Estrella Tipán, Dennis Angélica (2014)
The purpose of this thesis is to present the perceptions of students, teachers and authorities of the Salesiana University, Communication major on the valuation and depreciation of the Quichua language in the academic and social environment. Using a communicative product called "Documentary about the importance of the Quichua language students at the career of social communication." In academia, the Quichua language does not have the same level of importance as Spanish, causing diglossia since it exist a dominant language that displaces the Quichua language, despite being an official language of intercultural relations in Ecuador. With the creation of the Intercultural Bilingual Education in Ecuador it is intended to improve education, incorporating knowledge and skills that support the development of the individual, maintaining a balance between the modern and the ancient. Universidad Politecnica Salesiana adds to this process through Intercultural Bilingual Education race, which it has been developing since 1994.